The Future of Robotic Surgery: What to Expect from AI and Digital Health - Rasit Dinc (Rasit Dinc Digital Health & AI Research, 2024)
The Future of Robotic Surgery: What to Expect from AI and Digital Health The integration of robotics into surgical practice has fundamentally transforme...
Keywords: Digital Health; Diagnostics; Artificial Intelligence; Healthcare Innovation; Precision Medicine